Optimalisasi Sistem Penjadwalan Mata Kuliah Jurusan Bahasa Inggris Menggunakan Algoritma Genetika (Studi Kasus Politeknik Negeri Sriwijaya) - Siska Dwi Kristanti; Rasmila (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Scheduling courses is a problem that must be faced at every turn of the semester in every academic year at a university. The main problem is how to combine class, time, space, and teaching lecturers so that there are no clashes with each other. Currently, the English Department of the Sriwijaya State Polytechnic does not yet have a computerized scheduling system, so the scheduling process is still not effective and takes a long time. Based on these problems, an appropriate algorithm is needed, namely the genetic algorithm because it can shorten the time of making schedules and overcome schedule conflicts so that scheduling is more optimal. Specific rules in the genetic algorithm include population formation, individual fitness value calculations, selection calculations, crossbreeding processes, mutation processes and generation updates. The development method used is the RUP system. The programming language used is PHP and the database uses MySQL. The expected result of this research is an optimal course schedule and there are no clashes between courses, between lecturers, hours and time of lectures.